1980
DOI: 10.1159/000214335
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Relationships between Vitamin-K-Dependent Clotting Factors and Effective Hepatic Blood Flow, Albumin and Other Liver Function Tests

Abstract: Relationships between Normotest, prothrombin time, albumin, γ-globulin, GPT, and the hepatic fractional clearance of 198Au-colloids as a measure of effective hepatic blood flow were studied by correlation analysis, in 50 patients with liver diseases, including chronic hepatitis or cirrhosis. Simple correlation coefficients were highly significant between Normotest, prothrombin time, albumin, and the heaptic fractional clearance; however, not between GPT or γ-globulin and the other parameters. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…With regard to the relation ship between these blood coagulation param eters and HBF, our study only partially agrees with the investigation of Fujii et al [5] which showed a good correlation between HBF, Normotest, and serum albumin in pa tients with chronic liver disease. Our study seems to suggest that the correlation between HBF, serum albumin, and Normotest is only present in patients with severe hepatic fail ure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…With regard to the relation ship between these blood coagulation param eters and HBF, our study only partially agrees with the investigation of Fujii et al [5] which showed a good correlation between HBF, Normotest, and serum albumin in pa tients with chronic liver disease. Our study seems to suggest that the correlation between HBF, serum albumin, and Normotest is only present in patients with severe hepatic fail ure.…”
Section: Discussionsupporting
confidence: 83%
“…However, the mea sure of HBF with labeled colloid is consid ered an interesting test of hepatic function [3] . In fact, recent study showed that HBF reflects liver parenchymal volume of rat liver [4] and directly correlates with vitamin-Kdependent factors and serum albumin in pa tients suffering from chronic active hepatitis (CAH), chronic persistent hepatitis, and LC [5], These data suggested that albumin and vitamin-K-dependent factors can reflect the residual liver cell mass of patients affected by chronic liver disease [5]. This study, how ever, does not provide evidence for a differ ent correlation between HBF, Normotest, and serum albumin regardless of the type of chronic liver disease considered.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the two components of the ALBI score are selected on the basis of a mathematical model, but the five components of the CP score are selected empirically with arbitrary use of cutoff values and same weighting among all parameters. Further, there were correlations between components of the CP score such as albumin and international normalized ratio (both reflecting hepatic synthetic function) and albumin and ascites (decreased plasma osmotic pressure because of hypoalbuminemia) . Third, the CP score is designed primarily for cirrhotic patients, but a certain proportion of HCC arises from the non‐cirrhotic liver .…”
Section: Discussionmentioning
confidence: 99%
“…Further, there were correlations between components of the CP score such as albumin and international normalized ratio (both reflecting hepatic synthetic function) and albumin and ascites (decreased plasma osmotic pressure because of hypoalbuminemia). 14,15 Third, the CP score is designed primarily for cirrhotic patients, but a certain proportion of HCC arises from the non-cirrhotic liver. 16 Fourth, the cutoff values of bilirubin in the CP score are required to be modified for chronic cholestatic diseases such as primary biliary cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiment it may represent a lethal antagonism of adaptive hepatic growth, and in this view there would be an inverse relationship between liver size and vitamin K-dependent blood clotting in rats receiving hexoestrol and clomiphene. Such a relationship is belived to exist between the viable liver mass in humans with liver disease and the clotting time as determined by Normotest, a one-stage clotting assay derived from Thrombotest (Fujii et al,8) An effect on protein synthesis activity in the rough endoplasmic reticulum is regarded as one of the main actions of oestrogens on the liver (Adlercrettz and Tenhunen, 1). Action at this level may go some way to explain the physiological and pathophy-siological interrelations of oestrogens and vitamin K. This latter is a cofactor in the post-ribosomal carboxylation of glutamyl residues during the synthesis of clotting factors II, VII, IX and X (Gallop et zl., 9).…”
Section: Discussionmentioning
confidence: 99%